EDUKASI PENERAPAN ECOKIDS PADA SISWA SEKOLAH DASAR: WUJUD KONTRIBUSI SOSIAL PMM BATCH 4 UNIVERSITAS SAMUDRA - Fauzia, Arisna; Husna, Nidaul; Nur'aini, Nafiah; Amelia, Riska Dwi; Solikin, Rahmawati; Bahari, Laras Tika; Wardhana, Arya Kusuma; Husna, Husna (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This social contribution with the theme "Ecokids: Green Adventures Towards a Better Environment" was the result of the Independent Student Exchange Program (PMM). The community service activities were a real-life implementation of knowledge and experience of the Nusantara Module course. The PMM Batch 4 Inbound students at Samudra University, specifically group 1 “Seumantok” chose an elementary school as the community partner to carry out their service. From the initial survey conducted at school, some students did not understand the importance of environmental awareness and had low knowledge of sorting waste. The participants were 3rd grade elementary school students. The method used was by conducting education with presentations in class and using flip book learning media, games, and open discussions with the students. The results found that grade 3 students were able to learn about awareness and concern for keeping the environment cleaner. Apart from that, students were quite enthusiastic and could sort waste according to the type of waste, namely organic waste and inorganic waste.